Effect of Secretome Mesenchymal Stem Cells On Expression Interleukin 10 And Interleukin 17 in Mice Lupus Model - Nurudhin, Arif; Adnan, Zainal Arifin; Kertia, Nyoman (Bangladesh Journal of Medical Science, 2017)
Background: Systemic Lupus Erythematosus (SLE) is a chronic autoimmune inflammatory disease with extensive clinical features. The role of Interleukin 10 (IL-10) is to promote autoantibody production and autoreactive B cell proliferation. Interleukin 17 (IL-17) associated with pathogenesis of SLE and positively correlated with disease activity. Intraperitoneal pristane can induce lupus in mice. Mesenchymal stem cells secretome work in paracrine effects asantiinflammatory and immunomodulation agent by suppressing autoreactive T and B cell, which play an important role in pathogenesis of SLE. The aim of this study is to evaluate effect of mesenchymal stem cells secretome on the expression of IL-10 and IL-17 in murine lupus models induced by pristane. Methods: A randomized experimental study, post-test only control group design, samples using 21 female Mus Musculus mice strain Balb/C, divided into 3 groups: control group with intraperitoneal injection of 0.5 mL of 0.9% NaCl, treatment group with intraperitoneal injection of 0.5 mL pristane, therapy group with intraperitoneal injection of 0.5 mL pristane and 0.45 mL of secretome. Statistical analysis using ANOVA test. A p-value < 0.05 was considered statistically significant. Results: The results showed significant relationship between control and pristane groups both at the levels of IL-17 (control 6.9±1.95,pristane 9.9±2.27, pristane+secretome 6.1±1.95 p=0.016), and there are significant differences in the expression of IL-10 in the control group vs pristane group (-4,42±1,43 per 100 lymphocyte; p=0,006), pristane group vs pristane+secretome group (4,00±1,43 per 100 lymphocyte; p=0,012). Conclusion: Mesenchymal stem cells secretome decreased the expression of IL-10 and IL-17 levels in murine lupus models induced by pristane. Bangladesh Journal of Medical Science Vol.16(3) 2017 p.418-422